Legal Solution Overcoming the Problems in the Cases of Indonesian Republic Supreme Court - L Lufsiana (Fakultas Hukum, Universitas Warmadewa, 2018)
The accumulation of cases in the Supreme Court of the Republic of Indonesia, especially the case of the General Court (Civil and Criminal case) has not been resolved, even though there is an internal regulation that sets the time limit for the settlement of the case for 250 days and the division of rooms within the Supreme Court and the settlement takes a long time, it not only violates the legal principles of simple justice, fast and low cost even has opened the door of corruption, because the seeker of justice will try to speed up to get the verdict on his case. This paper provides a legal solution to the problem, namely by establishing representatives of the Supreme Court in every province in Indonesia and empowering the nation's children to become Supreme Court Justice (opening a wide field of employment for legal professionals) using the approach of legislation.